Systematic literature review on the use of narrative analysis in language education research - Yuzhen, Jin; Abdul Samad, Arshad; Noordin, Nooreen (Cosmos Scholars Publishing House, 2023)
Sociologists and communication theorists have defined narrative analysis as a way to form a social identity as early as the 1980s Barkhuizen, Benson, and Chik (2013). Besides, narrative analysis shares the concept of knowledge transmission, which is a theory that aims to communicate unquantifiable qualities of knowledge like experience and life stories. Nevertheless, it has not been specified how far the narrative analysis has gotten in language education studies due to varied understandings of the term. As a result, it is critical for researchers to conduct a more thorough literature assessment of narrative analysis in this discipline. This study examines the body of literature on narrative analysis in current language education studies. The method employed in this study is a systematic literature review, which includes pre-set criteria in selecting academic publications to be surveyed over a five-year period (1 January 2018 to 31 December 2022) and a qualitative synthesis of the findings. Based on a revised Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow, this study arrives at a holistic and systematic assessment of this approach over the last five years to guide future research in language education studies through description and analysis of the titles, abstracts, keywords, and full papers (when necessary) of the selected 10 academic articles out of 234. The main findings are as follows. 1?Narrative analysis is now used to investigate student identity creation and teacher professional development. 2?The majority of the current study's participants are non-English speaking teachers. 3) Typically, the sample size is no more than seven. 4) Text analysis and interviews are the two main research techniques. 5) Speaking and writing are the main topics of the current studies. 6)Due to its ability to elicit unique viewpoints, narrative analysis is used in language education research, but the amount is not high.